(untitled) (The São Paulo Journal of Mathematical Sciences, 2012)
For a flat Lie algebra g and a g-module M in a symmetric monoidal abelian category linear over a field of characteristic zero we establish and equivalence of categories between the groupoid of Lie algebra extensions of g by M and the groupoid of extensions in the category of g-modules of the augmentation ideal U(g)+by M.